Salvridge - Lim, Alexis (2016)
Food waste presents a threat to the environment because of greenhouse gas contributions and the wasted resources used to produce, process, market, transport and refrigerate food. In 2014, 788,600 tonnes of food waste was generated, of which 101,400 tonnes (13 per cent) was recycled. The rest of the food waste was disposed of at the incineration plants and then landfilled.